2010
DOI: 10.3233/jad-2010-1297
|View full text |Cite
|
Sign up to set email alerts
|

LPYFDa Neutralizes Amyloid-β-Induced Memory Impairment and Toxicity

Abstract: Misfolding, oligomerization, and aggregation of the amyloid-beta (Abeta) peptide is widely recognized as a central event in the pathogenesis of Alzheimer's disease (AD). Recent studies have identified soluble Abeta oligomers as the main pathogenic agents and provided evidence that such oligomeric Abeta aggregates are neurotoxic, disrupt synaptic plasticity, and inhibit long-term potentiation. A promising therapeutic strategy in the battle against AD is the application of short synthetic peptides which are desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 73 publications
2
12
0
Order By: Relevance
“…Future studies that inject Abeta right after fear conditioning might be able to distinguish between Abeta effects on learning and consolidation. Either way, our data are in line with previous studies that have reported effects of Abeta oligomers on learning and consolidation [13], [25], [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Future studies that inject Abeta right after fear conditioning might be able to distinguish between Abeta effects on learning and consolidation. Either way, our data are in line with previous studies that have reported effects of Abeta oligomers on learning and consolidation [13], [25], [26].…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that natural Abeta oligomers acutely impair the formation of a contextual fear memory is in agreement with previous studies that injected synthetic Abeta oligomers into the ventricle or hippocampus [25], [26]. In contrast, another study that injected synthetic Abeta oligomers into the hippocampus reported an improvement of contextual fear memory, suggesting that low levels of synthetic Abeta oligomers might have beneficial effects on memory [30].…”
Section: Discussionsupporting
confidence: 92%
“…Amyloids are highly sequence specific, and form stacked β-sheets of identical sequences in many molecules of the same protein [22], [23]. Therefore, amyloid formation is highly sensitive to addition of amyloid-forming or amyloid-interfering peptides with sequences identical to or slightly changed from the amyloid-forming region of the protein [48], [49]. An amyloid-forming peptide rescued the S. cerevisiae cells expressing Als5p V326N , as well as increasing surface amyloid levels in cells expressing Als5p WT and in C. albicans (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Linear amplification of RNA was performed (Amino Allyl MessageAmp II aRNA Amplification Kit; Ambion, Austin, TX) before labeling with Cy3 and Cy5 fluorescent dyes (GE Healthcare) and microarray hybridization to oligonucleotide arrays consisting of the Qiagen mouse MV3 oligo set with oligonucleotide length generally ∼70 nucleotides. General methods for data extraction, normalization, and filtration for quality and dye bias have been summarized in detail previously (21). Here data from three microarrays were analyzed in the National Cancer Institute mAdb microarray databasing system (http://madb.nci.nih.gov/) after standard Loess correction with an allowed quality ratio of 0.3.…”
Section: Oligo Microarray Hybridization and Data Analysismentioning
confidence: 99%